Military Sexual Trauma Among Women Veterans Using Veterans Health Administration Reproductive Health Care: Screening Challenges and Associations with Post-Military Suicidal Ideation and Suicide Attempts - Monteith, Lindsey L. (Journal of interpersonal violence, 2023)
Military sexual trauma (MST) is highly prevalent among women veterans. Research among MST survivors has focused on individuals receiving care in specific settings, such as mental health services. There is a dearth of knowledge regarding MST prevalence and associations in other settings commonly accessed by women veterans, including reproductive healthcare settings. We examined MST prevalence (overall, by MST type and extent of underreporting) and associations with suicidal ideation and suicide attempts, among women veterans accessing Veterans Health Administration (VHA) reproductive health care. Our sample included 352 post-9/11 women veterans who used VHA reproductive health care in Fiscal Year (FY) 2018 and participated in a cross-sectional survey. Approximately 68.7% screened positive for MST, including 44.9% who reported experiencing military sexual assault. Notably, 30.8% reported MST on the survey, but had a negative MST screen for their most recent MST screen in their VHA medical record. Both military sexual harassment and assault were associated with increased prevalence of experiencing suicidal ideation following military service; however, a significant association among military sexual harassment, past-month suicidal ideation, and post-military suicide attempts was not detected. Military sexual assault was uniquely associated with past-month suicidal ideation and post-military suicide attempts. As MST and underreporting are highly prevalent among women veterans using VHA reproductive health care, rescreening for MST within this population is essential. A trauma-informed approach is recommended irrespective of prior MST screening results and may facilitate suicide prevention in this population. Addressing barriers to MST disclosure and preventing MST and its sequelae remain critical.